2009
DOI: 10.1111/j.1748-5827.2009.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of quadriceps contracture in a dog using a static flexion apparatus and physiotherapy

Abstract: A four-month-old golden retriever developed quadriceps contracture following management of a comminuted femoral fracture with an intramedullary pin and cerclage wire. Management involved surgical release of the quadriceps, rigid stabilisation of the fracture, use of a static stifle flexion apparatus and postoperative physiotherapy. The dog returned to full activity with normal stifle function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In the cat described in this report, the tendon repair was protected with a flexion device. The use of such a device has been reported once before in a young dog with a quadriceps contracture (29). For the cat reported here, the device allowed full rangeof-motion of the hock with a controlled extension of the stifle.…”
Section: Discussionmentioning
confidence: 72%
“…In the cat described in this report, the tendon repair was protected with a flexion device. The use of such a device has been reported once before in a young dog with a quadriceps contracture (29). For the cat reported here, the device allowed full rangeof-motion of the hock with a controlled extension of the stifle.…”
Section: Discussionmentioning
confidence: 72%
“…Whilst various different physiotherapy regimens have been suggested for prevention of recurrence, the specifics are variable and there is little objective data reported (4,20). Intuitively the type and duration of physiotherapy probably plays a significant role in management of dogs with fibrotic myopathies and warrants further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…However, once the condition is advanced and fibrosis is established, the prog-nosis for restoring limb function without surgery is poor. [11][12][13] It has been reported that surgery itself may not be beneficial for all contractures; but, when it is performed, postoperative rehabilitation is particularly necessary to reduce the risk of recurrence due to scarring of transected tissues. [13][14][15] Degenerative joint disease In general, less is known about degenerative joint disease (DJD) in cats compared with dogs, even though there is radiographic evidence to suggest an incidence as high as 90% in geriatric cats, with the elbows predominantly being affected.…”
Section: Muscle Contracturementioning
confidence: 99%